2023
DOI: 10.1002/suco.202201026
|View full text |Cite
|
Sign up to set email alerts
|

The single and hybrid use of steel and basalt fibers on high‐temperature resistance of sustainable ultra‐high performance geopolymer cement mortars

Abstract: This paper primarily examines the flowability, physical appearance, mass loss, residual compressive strength (RCS), and residual flexural strength (RFS) properties of steel (ST) and basalt (BA) fiber-added sustainable ultra-high performance geopolymer cement (UHPGPC) mortars exposed to hightemperature effects. According to the results obtained, ST and BA fibers adversely influence the workability properties of UHPGPC mortars and thus significantly reduce the spreading diameters of the mortars. However, ST and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(3 citation statements)
references
References 102 publications
0
3
0
Order By: Relevance
“…As expected, Portland cement grouts are prone to cracking, but cracking can be reduced by incorporating fibers into the mix [ 47 ], since they provide better control of matrix cracking [ 47 , 48 , 49 , 50 ]. Some authors report that basalt microfiber (BF) in its current state of development can improve concrete durability by preventing early microcracks due to plastic shrinkage, and this effect is attributed to the reduction of the magnitude of free shrinkage, since basalt microfibers have a powerful bonding effect with the matrix and effectively restrict the development of micro- and macrocracks with their bridging effect [ 22 , 38 , 51 , 52 ]. Moreover, it has been reported that the risk of cracking is more prominent when the w/c ratio is reduced in the mix [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…As expected, Portland cement grouts are prone to cracking, but cracking can be reduced by incorporating fibers into the mix [ 47 ], since they provide better control of matrix cracking [ 47 , 48 , 49 , 50 ]. Some authors report that basalt microfiber (BF) in its current state of development can improve concrete durability by preventing early microcracks due to plastic shrinkage, and this effect is attributed to the reduction of the magnitude of free shrinkage, since basalt microfibers have a powerful bonding effect with the matrix and effectively restrict the development of micro- and macrocracks with their bridging effect [ 22 , 38 , 51 , 52 ]. Moreover, it has been reported that the risk of cracking is more prominent when the w/c ratio is reduced in the mix [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…[11][12][13][14] Geopolymers are inorganic polymers resulting from alkalination of an Al-Si-rich source material, forming tetrahedral polymeric structures. 15,16 The most common Al-Si source materials for geopolymer concrete synthesis are industrial wastes such as fly ash, silica fume, GGBFS etc. 17,18 The usage of waste materials in geopolymer concrete is an ideal solution to foster a circular economy in the concrete industry.…”
Section: Introductionmentioning
confidence: 99%
“…Another innovative solution to further mitigate CO 2 emissions amid an increase in concrete usage is to replace cement altogether with Alumino‐Silicate (Al‐Si) binders and develop a new type of concrete, that is, geopolymer concrete 11–14 . Geopolymers are inorganic polymers resulting from alkalination of an Al‐Si‐rich source material, forming tetrahedral polymeric structures 15,16 …”
Section: Introductionmentioning
confidence: 99%